“proceso de atención de enfermería en paciente de 26 años con diagnóstico de infección de vías urinarias (IVU) en el centro de salud la venus” - Martinez Rincon., Solange Briyid (2018)
Urinary tract infections are one of the most common complications of pregnancy and are responsible for an important percentage of both maternal and perinatal morbidity, this is due to functional, hormonal and anatomical changes so that the urethral meatus where it is located is exposed to bacteria and of the vagina that access the urinary tract, this disease being one of the main morbidity and mortality in our country. The following clinical study is a 26-year-old female patient of 16 weeks of gestation presenting dysuria, abdominal pain in the health center of Quevedo. The urinary tract infection is the existence of colonization and microbial growth, usually of bacterial origin, along the path of the urinary tract; that is, pyelonephritis if it affects the kidney and the renal pelvis, cystitis if it compromises the bladder, urethritis if there is involvement of the urethra and prostatitis if the infectious process is located in the prostate. The etiological agents may vary according to age, sex and underlying pathology. Each type of urinary tract infection can develop clinical manifestations, depending on the segment of the urinary tract that is infected. Kidneys (acute pyelonephritis): pain in the upper part of the back, and in the flank, hyperthermia, tremor, chills, nausea, vomiting Bladder (cystitis), pelvic pressure, pain in hypogastrium, frequent and painful urination, hematuria. Urethra (urethritis): dysuria, discharge.